PERAN BUDAYA ORGANISASI IPNU- IPPNU DALAM PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI KABUPATEN SLEMAN - Burhan Nudin (EL-TARBAWI, 2017)
This paper aims to discuss the role of organization culture of the Association of Nahdlatul Ulama’s Male and Female Students (Ikatan Pelajar Nahdlatul Ulama dan Ikatan Pelajar Putra Putri Nahdlatul Ulama/IPNU-IPPNU) in developing Islamic education in Sleman Regency. It argues that as student organization affiliated to an Islamic organization, IPNU-IPPNU has an important role to play in developing Islamic education among youth and students through their various programs and activities designed in accordance with their basic values and orientation as well as the advance of science and technology. Keywords: student organization, organizational culture, Islamic education